Obraba orodij pri odrezovanju z velikimi hitrostmi - Kopač, Janez (Strojniški vestnik, 2004)
Machining by cutting is strongly connected with wear on the tool's edge. The cutting-tool materials, the machined material, and the machining parameters have a direct influence on the toolćs wear grade and, of course, on the tool life. High speed machining (HSM) involves high cutting speeds, so that the classical, well-known principle S of tool-wear growth does not exist as before. There are some unpredictable matters.
Keywords: odrezavanje visokohitrostno; orodja rezilna; obraba orodij; materiali za orodja; orodja; odrezovanje; obraba